Peyote Shrines, Remembrance, and Ritual Surrogacy in South Texas - Hinojosa, Servando Z (Journal for the Study of Religion, Nature and Culture, 2024)
Peyote grows in South Texas where licensed dealers acquire it and sell it to Native American Church members. These dealers also create and maintain special shrines on their property for the visiting buyers. The shrines not only mark a portal of entry into the region but also comprise the only opportunity many Native Americans will have to see peyote growing in the ground. Prompting prayers and conversations about ‘relations’ back home, the shrines kindle many acts of remembrance, both between generations of visitors and between Native Americans and dealers. Moreover, the ways that Native Americans perform actions at the shrines that tie into rituals of thanks, gathering, and healing associated with other places underscores the shrines’ surrogate ritual importance. This matters for visitors who cannot access other ritual sites. By anchoring memories and challenging conventional thinking about agency, peyote shrines activate thinking about kindred while extending the ritualists’ reach into adjacent spaces.